An autopsy case of prostatic rhabdomyosarcoma with DICER1 hotspot mutation. Issue 1 (28th October 2020) - Miyama, Yu; Makise, Naohiro; Miyakawa, Jimpei; Kume, Haruki; Fukayama, Masashi; Ushiku, Tetsuo
Abstract : Somatic hotspot DICER1 mutations, which frequently coexist with germline inactivating mutation (i.e., DICER1 syndrome), have been identified in various types of benign and malignant conditions. Herein, we report an autopsy case of prostatic rhabdomyosarcoma (RMS) with a hotspot DICER1 c.5125G>A (p.D1709N) mutation. A 26 year‐old man presented with a prostatic mass, hematuria, and urinary retention. He underwent total pelvic exenteration, colostomy, ileal conduit construction and partial urethrectomy. Five months postoperatively, he developed multiple metastases to the lungs, brain, iliopsoas muscles and bones. He died of respiratory failure, and autopsy was performed. Microscopically, the tumor was primarily composed of uniform primitive mesenchymal cells infiltrating to the prostate with cambium layer. Rhabdomyoblasts and anaplastic cells were focally observed. Immunohistochemically, tumor cells were positive for desmin, myogenin, PAX7, HMGA2. Multinodular goiter was detected at autopsy. Because the morphology is similar to pleuropulmonary blastoma and DICER1 ‐mutant RMS of the female genital tract, we tested and identified a hotspot DICER1 mutation with Sanger sequencing. Recognizing DICER1 ‐mutant tumor is important because of its frequent association with germline DICER1 inactivation and potential therapeutic implication. Further research is needed to clarify whether this case can be classified as embryonal RMS with anaplasia or ' DICER1 ‐associated sarcoma'.